FACTORS RELATED TO PEOPLE’S PARTICIPATION IN SOLID WASTE MANAGEMENT IN NONG BUA SALA SUB-DISTRICT ADMINISTRATIVE ORGANIZATION, MUEANG DISTRICT, NAKHON RATCHASIMA PROVINCE - wangkhoklang, Suphap; Mokhunthod, Suparada (Primary Health Care Journal (Northeastern Edition), 2022)
The purpose of this descriptive research was to determine factors related to people’s participation in solid waste management in Nong Bua Sala sub-district administrative organization, Mueang district, Nakhon Ratchasima province. The samples were 310 family leaders selected by simple random sampling. The instrument for data collection was the questionnaire. The statistics used for data analysis were frequency, percentage, mean, standard deviation, maximum and minimum values, the Chi-Square test, and Pearson's Product Moment Correlation Coefficient. The research results revealed that the majority of the samples were female 63.9%, with an average age of 47.2 years, and 45.5% of them were 40-45 years old. 69.0% completed secondary school education, 66.1% worked in agriculture, and 60.6% had an average income of 12,842 baht per month. The sample group had a high level of knowledge about solid waste management, 85.0% had a high attitude toward solid waste management, 89.0%, and 89.7% had a high level of social support. Management of solid waste was at a high level of 59.4%. Factors related to occupation were related to people's participation in solid waste management with statistically significant (p-value<0.05) age, knowledge of solid waste management, and attitudes toward solid waste management there was a positive correlation between public participation in solid waste management with statistically significant (r = 0.313, 0.241 and 0.261, p-value < 0.05).